Syntactic Abnormalities in the Speech of Youth (Case Study of Complex Sentences Syntax) (Linguostylistic Studies, 2017)
The article highlights the polytypic syntactic abnormities at the level of the elementary complex and non-elementary complex sentences which are systemized in the article. The materials of the study have been selected from the spoken and written language of students and school seniors. The study has revealed the most common mistakes in regard with the formation of the relative clause, adverbial clauses, word order of the sentence and its components, choice of the normative conjunctions and connective words, syncretism of semantic-syntactical relations. The edited utterance variants are suggested.
Keywords: linguistic norms; linguistic mistake (abnormity); syntactic norms; syntactic mistake; elementary complex sentence and non-elementary complex sentence